Financial Performance of Pricol Limited in the ERP Environment - A Case Study - Sudalaimuthu, S.; Kanimozhi, N. (Gyan Management Journal, 2007)
Enterprise Resource Planning is the late t high-end solution. Information technology has lent to business application. The ERP solutions seek to streamline and integrate operation processes and information flows in the company to synergies the resources of an organization namely men, material, money and machine through information. Initially implementation of an ERP package was possible only for very large Multi National Companies and Infrastructure Companies due to high cost involved. Today many companies in India have gone in for implementation of ERP, which is expected in the near future that 60% of the companies will be implementing one or the other ERP packages since it will become a must for gaining competitive advantage. In this study ERP implementation in PRICOL Ltd was analysed with the following objectives: 1. To study the ERP system and its implementation in PRICOL Limited 2. To analyze the financial perlonnance R of PICOL Limited after the ERP system implementation.